THE PERCEPTIONS OF INDONESIAN SECONDARY EFL TEACHERS CONCERNING THEIR ROLES IN SYLLABUS DESIGN - Nita, Fatma Rahayu; Purwati, Oikurema (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2022)
In dealing with syllabus design, teachers must recognize their roles in syllabus design since they are taking part in it. Consequently, this current study attempts to explore Indonesian secondary EFL teachers concerning their roles in syllabus design. It covers three points: their general perceptions, their boundaries, and their qualification as the EFL teacher in syllabus design. The main theory used in this study is by Nunan (2000) related to the roles in syllabus design. This study applied a qualitative approach using open-ended questionnaires and virtual interviews as the instrument of the study. A total of five respondents have participated in this current study. The results found that the teachers believe that they have a role as the implementer and designer of syllabus design. Related to their boundaries in teaching English, all teachers create and develop the syllabus based on the student's needs. Besides, it discovers that teachers are likely to have the freedom to design their activities and materials based on the student's needs even though they should follow the basic element of the syllabus provided by the authorities. Finally, the teachers still need guidance and training in syllabus design since they have a fewer understanding of syllabus design.